Pengaruh Model Discovery Learning Terhadap Hasil Belajar Peserta Didik Pada Materi Ipa Di Kelas V Sd Negeri 13 Palangga Kabupaten Konawe Selatan - La Sisi (Prodi PGSD Unsultra, 2022)
This study aims to determine the effect of the Discovery Learning model on students’ learning outcomes in science subjects. The research employed a quantitative approach with a pre-experimental design of the One-Group Pretest-Posttest Design type. The subjects of this study consisted of 20 students. The results before the treatment showed that out of 20 students, 9 students (45%) achieved mastery, while 11 students (55%) did not, with an average pretest score of 66.20, categorized as low. After the treatment using the Discovery Learning model, 15 students (75%) achieved mastery, and 5 students (25%) did not, with an average posttest score of 77.00, categorized as high. Based on the results of inferential statistical analysis using the t-test, the significance value (2-tailed) was 0.003 < 0.05, indicating a significant difference between the pretest and posttest scores. Therefore, it can be concluded that the implementation of the Discovery Learning model has a positive effect on improving students’ learning outcomes in science subjects.